Cardiorespiratory Fitness Attenuates the Influence of Amyloid on Cognition. (19th November 2015) - Schultz, Stephanie A.; Boots, Elizabeth A.; Almeida, Rodrigo P.; Oh, Jennifer M.; Einerson, Jean; Korcarz, Claudia E.; Edwards, Dorothy F.; Koscik, Rebecca L.; Dowling, Maritza N.; Gallagher, Catherine L.; Bendlin, Barbara B.; Christian, Bradley T.; et al.
Abstract: The aim of this study was to examine cross-sectionally whether higher cardiorespiratory fitness (CRF) might favorably modify amyloid-β (Aβ)-related decrements in cognition in a cohort of late-middle-aged adults at risk for Alzheimer's disease (AD). Sixty-nine enrollees in the Wisconsin Registry for Alzheimer's Prevention participated in this study. They completed a comprehensive neuropsychological exam, underwent 11 C Pittsburgh Compound B (PiB)-PET imaging, and performed a graded treadmill exercise test to volitional exhaustion. Peak oxygen consumption (VO2 peak) during the exercise test was used as the index of CRF. Forty-five participants also underwent lumbar puncture for collection of cerebrospinal fluid (CSF) samples, from which Aβ42 was immunoassayed. Covariate-adjusted regression analyses were used to test whether the association between Aβ and cognition was modified by CRF. There were significant VO2 peak*PiB-PET interactions for Immediate Memory ( p =.041) and Verbal Learning & Memory ( p =.025). There were also significant VO2 peak*CSF Aβ42 interactions for Immediate Memory ( p <.001) and Verbal Learning & Memory ( p <.001). Specifically, in the context of high Aβ burden, that is, increased PiB-PET binding or reduced CSF Aβ42, individuals with higher CRF exhibited significantly better cognition compared with individuals with lower CRF. In a late-middle-aged, at-risk cohort, higher CRF is associated with a diminution of Aβ-related effects on cognition. These findings suggest that exercise might play an important role in the prevention of AD. ( JINS, 2015, 21, 841–850)